The Need for Improved Detection of Urinary Tract Infections in Young Children - Bunting-Early, Tracy E.; Shaikh, Nader; Woo, Lynn; Cooper, Christopher S.; Figueroa, T. Ernesto (Frontiers in Pediatrics, 2017)
Background and Objectives: An estimated 400,000 urinary tract infections (UTIs) are diagnosed annually in children aged <3 years in the United States; yet >50% of febrile UTIs may be missed in this population. Here we explored possible barriers to diagnosing febrile UTIs in very young children through social research of community pediatricians. Methods: Following qualitative interviews, a quantitative survey was developed that included a high-risk case for febrile UTI, presented before prompting for the topic of the survey, to gauge practice of delayed testing. Factors associated with delay were explored using univariate logistic regression. The final survey link was sent to 3 populations via email, with the largest response from a survey sent to pediatricians in Pennsylvania, which formed the basis of our primary results. Results: Of the 218 evaluable responses, 59.6% of physicians would initially test urine in the high-risk case patient, while 21.6% would choose to continue fever reducer and follow up in 2 days. In the knowledge-based questions, 67.5%, 34.0%, and 35.6% of respondents identified the correct prevalences in total population, Caucasian girls, and uncircumcised boys, respectively. Many pediatricians (59.5%) believed that delays in detection are common in clinical practice. Physicians who chose to delay testing were more likely to be female, in practice for <25 years, to underestimate prevalence of febrile UTIs, and have greater number of children seen per week (all P ≤ .02). Conclusion: Our findings support the need for improved communication and education about prevalence in higher risk populations, outcomes associated with delayed diagnosis, and optimal skills for collection of urine in young patients.